Investigation of the Students Behavior in Using Ride-Hailing Applications: Perspectives of Perceived Risk and Environmental Awareness in Technology Acceptance Model (TAM) - Silvani Febriliani; Jaka Nugraha; Jiunn-Woei Lian (Universitas Negeri Surabaya, 2025)
This study aims to provide an analysis of the influence of personal innovativeness on perceived ease of use and perceived risk, the influence of perceived ease of use and perceived risk on behavioral intention, and the influence of environmental awareness on behavioral intention. This study uses the Technology Acceptance Model (TAM) and was conducted on students in the Office Administration Education program from the 2021-2024 cohort, with a sample size of 274 students. Data analysis techniques employed Structural Equation Modeling (SEM)-Generalized Structured Component Analysis (GSCA) using the GSCA-pro software version 1.2.1.0. The results of this study indicate that personal innovativeness has a significant positive influence on perceived ease of use and perceived risk, perceived ease of use has a significant positive influence on behavioral intention, but perceived risk does not have a significant positive influence on behavioral intention, and environmental awareness has a significant positive influence on behavioral intention. This study contributes to the development of ride-hailing applications, particularly Gojek, in evaluating the determinants of behavior that influence user intent, as well as providing relevant supplementary learning material, particularly in related courses such as management information systems, organizational behavior, and office technology